Pengembangan Pengelolaan Proses Pembelajaran Matematika Di SMP Muhammadiyah 1 Surakarta - LASTIYONO, Hermawan; , Prof. Dr. Sutama, M.Pd (2015)
The research aims to describe about the develipment of Mathematic learning process management at Muhammadiyah 1 of Surakarta. That contains of medie used in Mathematic learning process at Muhammadiyah 1 of Surakarta, lesson material used in Mathematic learning process at Muhammadiyah 1 of Surakarta, teacher and students interaction in learning process Mathematic learning process at Muhammadiyah 1 of Surakarta, evaluation in Mathematic learning process at Muhammadiyah 1 of Surakarta. Research subjects are VII A grade at Muhammadiyah 1 of Surakarta that consist of 26 students. The research is development research, it'sbegin from certain problem that followed by action reserach class with 2 cycles, there are Mathematic learning process management and effectiveness measuremant by compare evaluation result before and after developing by teacher operation result. Research result, based on the result that done by researcher can be canclude that "moving media" indicode that student more courage to express their opinion. It is chowed by students ability to make some "bangun datar" share well, appropriate to creativity and their desire. The development of Mathematic learning process management by using NHT by developing DL show student more courage to express their opinion by finding their own way to more undestand interaction development by teacher to student show any increasing communication in student learning process management at Muhammadiyah 1 of Surakarta. Giving feedback ables to oncrease student learning result that showed by any differencess of vlue between condition before and after developing at Muhammadiyah 1 of Surakarta in VII A grade of Muhammadiyah 1 Surakarta in secand semester show the significant of learning result and show the effectiveness of in creasing result by using this approach.